Analyzing Undergraduate Students’ Critical Thinking Skill in Science Course - Dwi Sogi Sri Redjeki; Dede Mahdiyah; Noor Aisyah (Postgraduate, University of Mataram, 2023)
One of the most important skills to be mastered by the students in 21st century is Critical Thinking, specially in science matter. It belongs to the higher-order thinking skill which requires the students to have the ability to think logically, reflectively, productively and systematically in making consideration and finally making the best decision. In Indonesia, one of the purposes of education is to build the students who are independent and can think effectively and critically to solve problems in difficult situations. In order to support this idea, most of learning activity which asks the students to memorize needs to be replaced to the activity requiring the students to analyze and give the logical solution. In this study, the researcher tried to find the data related students’ critical thinking in the university. The descriptive quantitative is used to conduct this research. 50 undergraduate students were used as the subject of this research. The test given to the participants consisted of various categories such as C1, C2, C3, C4 and C5 which belongs to the Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS). Based on the findings, the critical thinking of undergraduate students belongs to high with 62.55%. The highest indicator of critical thinking skills are analysis and evaluation, while the lowest indicator is inference. It can be concluded that students’ critical thinking for undergraduate level after pandemic era are quite high as well as before the pandemic happened.